2016
DOI: 10.1097/j.pain.0000000000000767
|View full text |Cite
|
Sign up to set email alerts
|

Long-lasting antinociceptive effects of green light in acute and chronic pain in rats

Abstract: Treatments for chronic pain are inadequate, and new options are needed. Nonpharmaceutical approaches are especially attractive with many potential advantages including safety. Light therapy has been suggested to be beneficial in certain medical conditions such as depression, but this approach remains to be explored for modulation of pain. We investigated the effects of light-emitting diodes (LEDs), in the visible spectrum, on acute sensory thresholds in naive rats as well as in experimental neuropathic pain. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 87 publications
5
80
0
Order By: Relevance
“…Music has been shown to produce analgesia in humans (25-27, 80, 82, 134) and in rats (43). Recent studies also suggest analgesic activities of exposure to light in both humans and rats (135,136). The antinociceptive effects of the green LED light were associated with down-regulation of N-type calcium channels in dorsal root ganglion neurons, as well as were reversed by naloxone, thus also implicating the opioid-based analgesic mechanism (136).…”
Section: Translational Implications Of Studying Enriched Environmentmentioning
confidence: 98%
See 1 more Smart Citation
“…Music has been shown to produce analgesia in humans (25-27, 80, 82, 134) and in rats (43). Recent studies also suggest analgesic activities of exposure to light in both humans and rats (135,136). The antinociceptive effects of the green LED light were associated with down-regulation of N-type calcium channels in dorsal root ganglion neurons, as well as were reversed by naloxone, thus also implicating the opioid-based analgesic mechanism (136).…”
Section: Translational Implications Of Studying Enriched Environmentmentioning
confidence: 98%
“…Recent studies also suggest analgesic activities of exposure to light in both humans and rats (135,136). The antinociceptive effects of the green LED light were associated with down-regulation of N-type calcium channels in dorsal root ganglion neurons, as well as were reversed by naloxone, thus also implicating the opioid-based analgesic mechanism (136). Herein, we propose that studying combinations of multiple non-pharmacological modalities can lead to non-invasive and non-addictive treatments of pain ("digital analgesics") which can also result in lowering effective doses of analgesics and improving pain relief.…”
Section: Translational Implications Of Studying Enriched Environmentmentioning
confidence: 99%
“…Consequently, EE may help to reduce opioid consumption in pain management. Moreover, a pronounced decrease of the N‐type calcium channel, which governs excitatory neurotransmission, was detected in rats exposed to green LED light after nerve injury . The research infers that the reduction of calcium influx may also account for the antiallodynic and antihyperalgesic effects.…”
Section: Ee In Animal Models Of Neuropathic Painmentioning
confidence: 82%
“…Currently, 2 out of the 3 EE studies without a running wheel have shown a significant reduction in pain response following peripheral nerve injury (see Table ). One study has explored phototherapy for pain relief, which can be considered as a sole visual enrichment . Intriguingly, exposure to green LED light not only increased acute sensory thresholds to noxious thermal stimulus in naïve rats, but also reversed mechanical allodynia and thermal hyperalgesia in spinal nerve ligated rats.…”
Section: Ee In Animal Models Of Neuropathic Painmentioning
confidence: 99%
“…Migraine in particular often does not respond to traditional drugs including opioids. A recent study has shown some efficacy for a surprising therapy against migraine based on green light . The researchers bathed rats under LED light at various wavelengths in the visible spectrum for 8 h a day and compared their tolerance to neuropathic pain.…”
Section: Non‐drug Therapiesmentioning
confidence: 99%